2002
DOI: 10.4049/jimmunol.169.10.5458
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Nonspecific Recruitment of Th2 Cells to the Lung as a Mechanism for Viral Infection-Induced Allergic Asthma

Abstract: Respiratory viral infections have been shown to trigger exacerbations of asthma; however, the mechanism by which viral Th1-type inflammation exacerbates an allergic Th2-type disease remains unclear. We have previously shown that although adoptively transferred Th2 cells are inefficiently recruited to the lung in response to Ag, cotransfer of Th1 cells can increase accumulation of Th2 cells. In this study, we show that respiratory viral infection increases recruitment of resting Th2 cells specific for OVA even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 47 publications
6
52
0
2
Order By: Relevance
“…Thus, nonspecific recruitment of pre-established memory T cells to the lung airways appears to be a general feature of inflammation of the lung. However, the underlying mechanism of recruitment remains to be elucidated, although emerging data indicate that monocyte chemoattractant protein 1, RANTES, monocyte IFN-␥-inducible protein, and cytokine-responsive gene 2 may play key roles (28,40,41). We are currently investigating the impact of inflammatory chemokine production on the nonspecific recruitment of memory CD8 ϩ T cells during heterologous infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, nonspecific recruitment of pre-established memory T cells to the lung airways appears to be a general feature of inflammation of the lung. However, the underlying mechanism of recruitment remains to be elucidated, although emerging data indicate that monocyte chemoattractant protein 1, RANTES, monocyte IFN-␥-inducible protein, and cytokine-responsive gene 2 may play key roles (28,40,41). We are currently investigating the impact of inflammatory chemokine production on the nonspecific recruitment of memory CD8 ϩ T cells during heterologous infection.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that respiratory virus infections induce an increase in the numbers of heterologous memory CD8 ϩ T cells in the lung or lung airways (14,19,28). However, it was not clear whether this reflected local proliferation or recruitment of cells from other sites.…”
Section: Sendai Virus Specific Memory Cells In the Lung Airways Incrementioning
confidence: 97%
“…35,36 Paradoxically, Th2 cells clearly have the potential to migrate into lung tissue in the presence of a strong inflammatory signal, as suggested by the tendency for respiratory infections to exacerbate asthma. 37 With the recent discovery of a third T-cell subset (Th-17 cells) regulated by IL-23, which is of particular importance in the inflammatory response, there is clearly a need for further detailed studies on the signals that control the trafficking of T-cell subsets and their importance in the expression of vaccine-induced pulmonary immunity. 38 Our study demonstrates a profound influence of the Th1/Th2 balance on the developmental kinetics as well as on the structure and cellular composition of the granuloma during infection.…”
Section: Discussionmentioning
confidence: 99%
“…This signals cDCs to produce CCL28 and recruit eff ector Th2 cells. Because Th2 recruitment to the lung is antigen nonspecifi c, it is possible that this mechanism contributes in other ways to allow the innate immune system to infl uence the antiviral response ( 36 ). For example, regulatory T cells express CCR10 and may be another important target of CCL28 ( 37 ).…”
Section: Blockade Of Ccl28 Inhibits Postviral Mucous Cell Metaplasiamentioning
confidence: 99%